The Effect of Parental Education Patterns on Attitudes and Learning Outcomes of Elementary School Students in the Pandemic - Margaretha Sugiyanti; Rian Vebrianto; Siti Aisyah (Instructional Development Journal, 2023)
This article aims to analyze the influence of parents' educational patterns on attitudes and student learning outcomes. The type of research used is a quantitative approach with the ex post facto method. The population in this article is all fourth grade students at SDN in the Lubuk Batu Jaya sub-district, totaling 461 people. By using proportional stratified random sampling, a sample of 83 people was obtained. The instruments used were a questionnaire on parents' educational patterns and student learning attitudes, and documentation of student learning outcomes. The results of distributing questionnaires and documentation of learning outcomes were analyzed using parametric statistics, namely simple linear regression. Based on the research results obtained data regarding the influence of the family environment on the formation of children's character, it can be concluded that: 1) there is an influence of parental education patterns on students' learning attitudes of 12.3% and 87.7% influenced by other factors; 2) there is an influence of parental educational patterns on results student learning of 4.7% and 95.3% is influenced by other factors; and 3) there is an influence of learning attitudes on student learning outcomes of 3.6% and 96.4% influenced by other factors.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersianÂ // Â TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//